Dukungan Suami dan Bonding Attachment dengan Kelancaran ASI Ibu Nifas : Studi Korelasional - Laura Fernandia; Marcelina, Sheilla Tania (Jurnal Medicare, 2025)
Breastfeeding provides health, psychological, social, and economic benefits for both mothers and babies. However, despite the WHO's global target to increase exclusive breastfeeding coverage, Indonesia has seen a decline. The main obstacles include lack of social support, ongoing education, and low maternal motivation and confidence. Husband support plays a vital role in the mother's psychological well-being and milk ejection reflex. This study aims to examine the relationship between husband support and bounding attachment with smooth breast milk production in postpartum mothers. A cross-sectional study was conducted involving 43 postpartum mothers at Purwodadi Health Center, Malang, using questionnaires and analyzed with Chi-Square and Fisher exact tests. Results showed 77% of mothers received low husband support, 51% had low bounding attachment, and 60% reported smooth milk production. There was a significant relationship between husband support (p=0.003) and bounding attachment (p=0.039) with milk production. In conclusion, strong husband support and good bounding improve breast milk flow.